Segregation behaviors in {101¯1} compressive twin boundaries of Mg-RE alloy under deformation at room temperature - Yujie Cui; Lili Guo; Yunwei Gui; Kenta Aoyagi; Haotian Tong; Qinqin Wei; Fangzhou Liu; Yuichiro Hayasaka; Akihiko Chiba (Journal of Magnesium and Alloys)
Solute atoms and precipitates significantly influence the mechanical properties of Mg alloys. Previous studies have mainly focused on the segregation behaviors of Mg alloys after annealing. In this study, we investigated the segregation behaviors of an Mg-RE alloy under deformation. We found that the enrichment of solute atoms occurred in {101¯1} compressive twin boundaries under compression at 298 K without any annealing in an Mg-RE alloy by scanning transmission electron microscopy and energy-dispersive X-ray analysis. The segregated solutes and precipitates impeded the twin growth, partially contributing to the formation of small-sized {101¯1} compressive twins. This research indicates the twin boundaries can be strengthened by segregated solutes and precipitates formed under deformation at room temperature.